Replication Report: A Comment on "Politicians' Private Sector Job and Parliamentary Behavior" - Rachel Ganly; Lukas Lehner; P. Linh Nguyen; Alex Sutherland (Institute for Replication (I4R), 2025)
Weschle (2024) examines the effect of UK legislators taking private sector jobs while holding office on their parliamentary behaviour. The published analysis employs two-way fixed effects and difference-in-differences as an identification strategy. In that analysis, which we were able to computationally reproduce from the data and code provided, the author found that holding a private sector job meant that: (i) overall MPs are 0.1% more likely to rebel against their party, with most of that effect driven by Conservative MPs who are 0.2% more likely to rebel but overall there is a minimal impact on rebellion and this is significant at the 10% level (p 0.069). The original results also show (ii) that 'moonlighting' MPs are also likely to attend more votes, estimated at 2.2% more compared to pre-employment levels (b 0.022, se 0.008, p 0.008), with the result again driven by Conservative MPs (b 0.028, se 0.011, p 0.010). The final set of results show that (iii) overall MPs who are employed are statistically significantly more likely to ask parliamentary questions (b 0.375, se 0.079, p 0.00001, with the effect again concentrated in Conservative MPs who were 60% more likely to ask a parliamentary question following employment (b 0.455, se 0.098, p 0.00001). Overall, the replication package was well-organized, and the analysis could be fully reproduced using the provided cleaned data. Further, the main outcomes proved consistent across a number of robustness checks.
Keywords: 330